ALDH2 gene G487A polymorphism and coronary artery disease: a meta‐analysis including 5644 participants. Issue 3 (26th December 2017) - Li, Yan‐yan; Wang, Hui; Wu, Jing‐jing; Kim, Hyun Jun; Yang, Xin‐xing; Geng, Hong‐yu; Gong, Ge
Abstract: Several studies indicate the mitochondrial Aldehyde Dehydrogenase‐2 (ALDH2) gene G487A polymorphism may be correlated with coronary artery disease (CAD) susceptibility, but a clear consensus has yet to be reached. To elucidate the relationship between the ALDH2 gene G487A polymorphism and CAD within the Chinese population, a meta‐analysis of 5644 subjects from nine individual studies was performed. Pooled odds ratios (ORs) and their corresponding 95% confidence intervals were assessed using random or fixed‐effect models depending the heterogeneity existence or not. Our meta‐analysis found a significant association between ALDH2 gene G487A polymorphism and CAD in the Chinese population under allele (OR: 1.830, 95% CI: 1.560–2.140, P = 1.36 × 10 −13 ), recessive (OR: 1.920, 95% CI: 1.530–2.390, P = 1.20 × 10 −8 ), dominant (OR: 1.593, 95% CI: 1.336–1.900, P = 2.22 × 10 −7 ), homozygous (OR: 2.280, 95% CI: 1.810–2.870, P = 3.17 × 10 −12 ) and heterozygous genetic models (OR: 3.330, 95% CI: 2.070–5.370, P = 7.81 × 10 −7 ). The positive correlation between the ALDH2 gene G487A polymorphism and CAD makes the mutation a strong candidate as a genetic risk marker for CAD. Through further analysis, we also found that A allele carriers of ALDH2 gene G487A polymorphism may be particularly susceptible to CAD.